PROCEDURAL SUCCESS AND IN HOSPITAL COMPLICATIONS OF CHRONIC TOTAL OCCLUSION PERCUTANEOUS CORONARY INTERVENTION - Waleed, Mohammad; Raza, Ali; Shahzeb; Alishan, Syed; Abidullah; Akbar, Fazal; Masoud, Maryum; Rafi Ullah Jan (Journal of Ayub Medical College Abbottabad, 2025)
Background: Chronic total occlusion (CTO) recanalization had been considered as technically challenging procedure with low chances of successful recanalization. The aim this study is to find out the rate of procedural success and complications associated with revascularization of CTO. Methods: This is a retrospective observational study. Records of 243 patients presenting to Peshawar Institute of Cardiology were analyzed form 1st April 2021 till 31st March 2024, who had PCI for CTO lesions. Results: Among 243 patients analyzed 70.4% were male and 29.6% were females. J-CTO score was used to assess the complexity of the lesion. Mean J-CTO score was 2.4±0.97. LAD was the commonest CTO vessel requiring revascularization. Highest success rate (95%) was seen with “easy” lesions (J-CTO <1) and shows a significant association at p value >0.05. Overall complication rate was very low. Two patients (0.82%) had mortality. Coronary perforation was the gravest complication. Conclusion: CTO recanalization is a complex procedure which requires different skillset. Our success rate is lower than international figures which emphasizes on the necessity of advanced training in this domain of coronary intervention. Fortunately, our complication rate closely resembles to global data ensuring safety of our procedures.